Produksi Pembuatan Briket Arang Dari Pengolahan Limbah Tempurung Kelapa Sebagai Sumber Energi Terbarukan - Miftahul Cahyo Nugroho; Siti Fatimah Nurhayati (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
The use of fossil fuels as an energy source is depleting due to the increasing need for use. Alternative solutions such as renewable energy sources are implemented to minimize dependence on fossil fuels. Coconut shell waste is biomass that can be used as a renewable energy source. Coconut shell waste produced from coconut plants can be converted into charcoal briquettes. The production process involves steps such as getting raw materials on the market, drying raw materials, burning, grinding, mixing with adhesive, molding, and drying briquettes. Efforts to process coconut shell waste as a sustainable renewable energy source by producing charcoal briquettes from this waste can produce an alternative energy source that is both economical and environmentally friendly. Apart from that, using coconut shell waste for energy can help reduce negative impacts such as environmental pollution due to the use of fossil fuels.